The role of the clinical pharmacist in patient education and monitoring of patients under warfarin treatment - SANCAR, MESUT; TEZCAN, SONGÜL (MARMARA UNIV, 2019)
This study was carried out on patients who were under anticoagulation treatment with warfarin, at the outpatient cardiology clinic. The aim was to determine the effectiveness of pharmacist consultation, education, and intervention on each patient's therapeutic results. A cross-sectional randomized trial has been done. Twenty-five patients were included in the study. The Oral Anticoagulation Knowledge (OAK) Test, Short Form-36 (SF-36) and Duke Anticoagulation Satisfaction Scale (DASS) were applied. Patients resumed their routine anticoagulation treatment and INR and complications were recorded during the study. Additionally, patients received patient education, consultation on lifestyle and anticoagulant usage issues from a pharmacist. The same tests were applied again to the patients on the 90th day of the study and the results were compared with the initial test. Maintenance of INR within the target range and complication rates were compared before and after the intervention. Pre-test and post-test results of the patients revealed statistically significant improvements on the physical and mental score components of the SF-36 (p = 0.001; p = 0.001), OAK test scores (p <= 0.001) and the (negative) limitations and burdens and positive effects components of the DASS (p = 0.005; p < 0.001; p = 0.001). The successful maintenance of INR within target range was significantly higher (p = 0.027). The positive effects of pharmacist consultation and education on therapeutic results were demonstrated.
Keywords: Warfarin; anticoagulation; monitoring; clinical pharmacist; QUALITY-OF-LIFE; ANTICOAGULATION KNOWLEDGE; ORAL ANTICOAGULATION; OLDER PATIENTS; THERAPY; IMPACT; IMPLEMENTATION; MANAGEMENT